Invasive crayfishes as a threat to freshwater bivalves: Interspecific differences and conservation implications - Meira, Alexandra (2018)
Freshwater bivalves have suffered major global declines, being the introduction of invasive alien species (IAS) an important, but not well studied, mechanism of threat. This study assessed the predator-prey relationship between two non-native crayfish species (Procambarus clarkii and Pacifastacus leniusculus) and three native (Anodonta anatina, Potomida littoralis and Unio delphinus) and one non-native (Corbicula fluminea) freshwater bivalve species through experiments in laboratory and validation under natural conditions (Sabor River basin, Portugal). All native bivalve species were preyed both in laboratory and in the field; however, both crayfish species were unable to prey C. fluminea. Predation was dependent on crayfish and bivalve species but was not affected neither by crayfish nor bivalve sizes. In the laboratory, the most preyed species by both crayfishes was A. anatina. On average, this species was preyed at least 12% more than other species, when crayfishes had a choice. Similar results were found in the field. We also found signs of competition between both crayfishes, being P. clarkii more dominant and aggressive as this species, on average, manipulated the bivalves 63.6% more times and 24:33 min longer than P. leniusculus, and initiated 55.8% more agnostic bouts. Our results support the idea that P. clarkii and P. leniusculus can affect native freshwater bivalves, but clear interspecific differences were detected. Both crayfishes may have direct and indirect impacts on bivalve populations by increasing mortality or by reducing their fitness. In addition, since both crayfishes do not prey C. fluminea, they offer this IAS another advantage over native bivalves. Given the widespread distribution of both P. clarkii and P. leniusculus and the threatened status of many freshwater bivalves, the dynamics and impacts of this relationship should be taken in account in the implementation of management measures devoted to the conservation of native freshwater bivalves.